Molecular adhesion controlled microelectromechanical memory device for harsh environment data storage - Chua, Geng Li (2015)
This work demonstrates a cantilever based electrostatic microelectromechanical system device operating as a memory element. Volatile and non-volatile functions are engineered by manipulating molecular adhesion force through contact dimples and restoring force using the cantilever design. For non-volatile RESET operation, a method of detaching the cantilever with 3 V pulsating DC signal at 1 MHz is proposed. SET/RESET cycles are performed up to 103 times at 300 °C without any performance degradation. A writing speed of up to 0.94 μs is achieved, which is faster than conventional high temperature flash memories. With demonstrated attributes, the fabricated device offers excellent potential for harsh environment data storage applications.